Impact of Institutional Quality and International Trade on the Performance of the Nigerian Economy - Samson, Eniekenumu Brafiya (Faculty of Natural and Applied Sciences Journal of Basic and Environmental Research, 2025)
This study investigates the effect of institutional quality and international trade on the performance of the Nigerian economy, measured by real gross domestic product (RGDP). The independent variables examined include exchange rate (EXR), corruption perception index (CPI), exports (EXP), imports (IMP), government effectiveness (GE), and gross capital formation (GCF). Stationarity of the data was confirmed using the Augmented Dickey-Fuller (ADF) test, which showed that all variables were stationary at level [I(0)]. Consequently, the Ordinary Least Squares (OLS) regression technique was employed. The empirical results indicate that exports, imports, and gross capital formation have statistically significant positive impacts on RGDP, while exchange rate and government effectiveness show negative but insignificant pact on RGDP. Similarly, the corruption perception index was found to have an insignificant negative relationship with RGDP, suggesting that perceived corruption may dampen growth. The study recommends policies aimed at boosting trade performance through export diversification, minimizing reliance on consumer goods imports, increasing capital investment in productive sectors, and strengthening institutional frameworks to reduce corruption and improve economic governance.